The Etymology of Several Armenian Words Derived from PIE Root *(a)u̯(e)- «True, Faithful» - Zakaryan, Hovhannes (Bulletin of Yerevan University B: Philology, 2024)
The article is devoted to the etymology of a number of Armenian words or roots that derived from the PIE root *(a)u̯(e)- “true, faithful” and in written Armenian begin with the sound(s) վ- or (հ)աւ-. Etymologies were carried out on the basis of phonetic, lexical, semantic analyses, using methods of internal and external reconstructions and comparative-historical research. Materials included in well-known etymological dictionaries and studies, as well as in dictionaries of Armenian dialects, were used. In Indo-European studies it is generally accepted that the Armenian words with the initial sound վ- are non-original, with the exception of about a dozen words that are considered deviations from the norm. The present article reveals the regularity of the origin of native (inherited) Armenian words with the initial sound վ-, due to which new etymologies are put forward. Within the framework of the article puts forward the new etymologies of following words: վավեր, վստահ, հաւատ, հավաստ, հաւասար, ապաւէն. These new etymologies are the contribution of the author.